Biomechanical Determinants Influencing Smash Performance in Racket Sports from 2000 to 2024: A Systematic Review and Meta-Analysis - Kumar, Sunil; Das, Ratna (Physical Education Theory and Methodology, 2024)
Objectives. This systematic review and meta-analysis study aimed to evaluate the biomechanical determinants influencing smash performance in racket sports from 2000 to 2024. The study focuses on kinematic, kinetic, and neuromuscular factors that contribute to effective smash execution. Materials and Methods. A comprehensive literature search was conducted across PubMed, Scopus, and Web of Science, yielding 247 articles, of which 9 met the inclusion criteria. The included studies were analyzed for key biomechanical determinants, with a focus on joint angles, limb velocities, trunk rotation, muscle forces, ground reaction forces (GRFs), joint torques, and muscle activation patterns. Meta-analysis was performed to determine pooled effect sizes and assess heterogeneity. Results. The meta-analysis revealed significant positive effects of biomechanical determinants on smash performance. Kinematic factors such as joint angles and trunk rotation (X-Factor) had the highest impact, with a pooled effect size of 1.20. Kinetic determinants, including muscle forces and GRFs, also showed substantial effects (pooled effect size of 1.10). Neuromuscular factors, which are crucial for muscle activation and coordination, had a pooled effect size of 1.15. Fatigue was found to significantly reduce performance metrics, highlighting the need for fatigue management in training programs. The heterogeneity was low to moderate, indicating consistency across studies. Conclusions. The findings underscore the importance of optimizing biomechanical factors to enhance smash performance. Training programs should focus on improving joint angles, limb velocities, trunk rotation, muscle forces, and coordination. Fatigue management strategies are essential to maintain performance levels. These insights provide a foundation for developing targeted training programs to improve athletic outcomes in racket sports.